A review of the global burden, novel diagnostics, therapeutics, and vaccine targets for cryptosporidium. Issue 1 (January 2015) - Checkley, William; White, A Clinton; Jaganath, Devan; Arrowood, Michael J; Chalmers, Rachel M; Chen, Xian-Ming; Fayer, Ronald; Griffiths, Jeffrey K; Guerrant, Richard L; Hedstrom, Lizbeth; Huston, Christopher D; Kotloff, Karen L; et al.
Summary Cryptosporidium spp are well recognised as causes of diarrhoeal disease during waterborne epidemics and in immunocompromised hosts. Studies have also drawn attention to an underestimated global burden and suggest major gaps in optimum diagnosis, treatment, and immunisation. Cryptosporidiosis is increasingly identified as an important cause of morbidity and mortality worldwide. Studies in low-resource settings and high-income countries have confirmed the importance of cryptosporidium as a cause of diarrhoea and childhood malnutrition. Diagnostic tests for cryptosporidium infection are suboptimum, necessitating specialised tests that are often insensitive. Antigen-detection and PCR improve sensitivity, and multiplexed antigen detection and molecular assays are underused. Therapy has some effect in healthy hosts and no proven efficacy in patients with AIDS. Use of cryptosporidium genomes has helped to identify promising therapeutic targets, and drugs are in development, but methods to assess the efficacy in vitro and in animals are not well standardised. Partial immunity after exposure suggests the potential for successful vaccines, and several are in development; however, surrogates of protection are not well defined. Improved methods for propagation and genetic manipulation of the organism would be significant advances.